Peer passenger intentions to speak up to a risky driver: A theoretically-guided investigation of the effects of a high school road safety education program. (April 2018) - Kennedy, A.; Cullen, B.; Firman, D.; Fleiter, J.J.; Lewis, I.
Highlights: Theory-based investigation of a high school road safety education program. Passenger intentions to speak up to driver using their mobile phone as key outcome. Program exposure associated with increased intentions relative to a Control group. TPB constructs and anticipated regret as predictors of intentions. EPPM constructs highlighted influence of gender and different threats in persuasion. Abstract: Young drivers aged 17–25 years are over-represented in road crashes, with young males being nearly three times more likely to be involved in a road crash than females. In Australia, young drivers are also more likely to use their mobile phone while driving, with distraction from such use representing a major contributing factor to crashes. This study examined high school students' responses to a school-based road safety program, namely, the Royal Automobile Club of Queensland's (RACQ) Docudrama Program. Two theoretical frameworks underpinned the investigation, the Extended Parallel Process Model (EPPM) and an extended Theory of Planned Behaviour (TPB). These frameworks assisted in the identification of key constructs that may help to explain how the program influences young people's intentions to speak up to a driver engaging in a risky behaviour; specifically, talking on their mobile phone while driving. A between-groups design compared responses from students exposed to the program (i.e., the Intervention group) with those of students yet to be exposed (i.e., the Control group). Overall, the findings indicated that students who experienced the program reported greater intentions to speak up, as a passenger, to a friend who was using their mobile phone while driving. The EPPM-based results highlighted that gender influences the program's effects and that a focus on the social threat of receiving social disapproval for risky driving may be important for increasing the persuasiveness of the program for young males. The results in relation to the key TPB constructs identified anticipated regret and perceived behavioural control as important predictors of passenger intentions to speak up. Although the results provided support for the beneficial effects of program exposure, the implications of the research are discussed in terms of some potential modifications which may enhance the program's persuasive effects.